Internet Survey Evaluation of Iliopsoas Injury in Dogs Participating in Agility Competitions - Fry, Lindsey M.; Kieves, Nina R.; Shoben, Abigail B.; Rychel, Jessica K.; Pechette Markley, Arielle (Frontiers in Veterinary Science, 2022)
Objective: To describe risk factors associated with demographics, training, and competition for iliopsoas injury in dogs participating in agility competitions, as well as describe owner reported treatment and return to sport following injury. Procedures: An internet-based survey of agility handlers collected risk factor data for dogs partic-ipating in agility. Owners were asked questions about demographics, training, and competition as well as injury treatment and recovery if applicable. Associations between variables of interest and iliopsoas injury were estimated with logistic regression. The final risk factor model was built via modified backward selection, with all variables in the final model showing significant associations at p<0.05. Results: Of the 4,197 dogs in the sample, 327 (7.8%) reported iliopsoas injury. The final model identified six risk factors for iliopsoas injury. A higher risk of iliopsoas injury was observed for the Border Collie breed, dogs with handlers who are veterinary assistants, dogs competing on dirt, dogs competing on artificial turf 6+ times a year, and dogs that trained with the 2x2 method for weave poles. Dogs that were not acquired with agility in mind were observed to have a decreased risk of injury. Factors like number of competition days and jump height were not significantly as-sociated with risk of iliopsoas injury. Owners sought veterinary care for 88% of dogs with iliop-soas injury, including specialty care for 63%. Treatment most often included rest, home rehabilita-tion, formal rehabilitation, and/or oral medications. Most dogs (80%) were able to return to sport within 6 months, while 20% were out for longer than 6 months, or retired. Conclusion and Clinical Relevance: Iliopsoas injury can necessitate a significant amount of time off from training and competition, and even lead to retirement of dogs competing in agility. Some of the risk factors identified in this study can inherently not be modified (breed, intended use, and handler profession), but can be taken into consideration for injury prevention strategies. Competi-tion and training risk factors that can be modified, such as weave training, may help to inform guidelines for best practices in management of the agility athlete.